Modelling Ontology of Craft Convection as Small and Medium Enterprises - Ari Fajar Santoso; Ahmad Suryan (The Indonesian Institute of Science and Technology Research, 2022)
Knowledge elicitation is a process to obtain and transfer knowledge (that is, for example, accumulated inside the minds of experts in a certain domain) from humans to abstract and effective representations, to organize, model, and ultimately, communicate it in such form that is easier to understand and utilized through formal representation. Knowledge elicitation uses ontology approach so that knowledge representation can be presented in knowledge management system. This knowledge will be utilized mainly in Craft Convection Small Medium Enterprises (SMEs). Ontology as an instrument to represent knowledge has been studied and applied in various fields such as information science, knowledge engineering, artificial intelligence, or digital library. In the field of ontology and design, ontology can be applied in knowledge sharing. Using methontology approach, ontology modeling and implementation are developed to identify patterns and concepts of knowledge related to Craft Convection SMEs.